2021
DOI: 10.3389/fspor.2021.725245
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Machine-Learning-Based Classifier for the Identification of Head and Body Impacts in Elite Level Australian Rules Football Players

Abstract: Background: Exposure to thousands of head and body impacts during a career in contact and collision sports may contribute to current or later life issues related to brain health. Wearable technology enables the measurement of impact exposure. The validation of impact detection is required for accurate exposure monitoring. In this study, we present a method of automatic identification (classification) of head and body impacts using an instrumented mouthguard, video-verified impacts, and machine-learning algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 42 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Mouthguards were found to have an overall sensitivity ranging from 69.2% to 100% and a positive predictive value ranging from 55.0 to 96.4% depending on the device, minimum impact threshold, and data processing technique [ 85 , 86 , 88 , 89 ]. Using a series of untuned classifiers, one study reported an average true positives rate of 77.84% and a true negative rate of 89.55% [ 91 ]. The best classifier identified was an XGBoost-based model with true positive rates ranging from 94.67 to 100% and true negative rates ranging from 95.65 to 96.83% depending on the used dataset [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouthguards were found to have an overall sensitivity ranging from 69.2% to 100% and a positive predictive value ranging from 55.0 to 96.4% depending on the device, minimum impact threshold, and data processing technique [ 85 , 86 , 88 , 89 ]. Using a series of untuned classifiers, one study reported an average true positives rate of 77.84% and a true negative rate of 89.55% [ 91 ]. The best classifier identified was an XGBoost-based model with true positive rates ranging from 94.67 to 100% and true negative rates ranging from 95.65 to 96.83% depending on the used dataset [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using a series of untuned classifiers, one study reported an average true positives rate of 77.84% and a true negative rate of 89.55% [ 91 ]. The best classifier identified was an XGBoost-based model with true positive rates ranging from 94.67 to 100% and true negative rates ranging from 95.65 to 96.83% depending on the used dataset [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…This, once again, illustrates the need to additionally verify or filter sensor recordings by secondary sources of information in order to obtain reliable exposure data 16 , 17 . Since previous studies demonstrated the potential of data-driven machine learning models for the identification of various types of head impacts in both American 26 , 27 and Australian rules football 28 as well as soccer 29 , 30 , we used an LSTM neural network for the automatized detection of header events as the most common type of RHI in the game of soccer 19 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…While their algorithm was able to correctly classify 88% of all sensor-recorded events, only half (51%) of the predicted impacts actually corresponded to actual head impacts (precision) 25 . In actual sporting contexts, most approaches focused on the discrimination between true head impacts and non-impacts in American 26 , 27 or Australian rules football 28 . While the models employed by Wu et al 26 (support vector machine, SVM) and Gabler et al 27 (Adaboost) achieved classification performances ranging from 68.5% to 93.8% and 81.6% to 98.3%, respectively, the best-performing classifier (XGBoost) in the study of Goodin et al 28 showed promising impact and non-impact detection rates of approx.…”
Section: Introductionmentioning
confidence: 99%
“…Recent attempts have been made to accurately quantify and monitor a player's in-game exposure to direct and indirect head impacts in collisions sports via accelerometry (50,51). These devices use linear acceleration magnitude threshold of >5g (52) or ≥10g (50,51,53) to identify an impact event. These thresholds are well above this current study's average peak linear acceleration magnitude reported but are not too dissimilar to a recent in-game study of professional rugby league players tackling (linear (median, 7.1g; Q1, 5.2g; Q3, 9.9g) and angular acceleration (median, 0.6 krad•s −2 ; Q1, 0.4 krad•s 2−1 ; Q3, 0.9 krad•s −2 )).…”
Section: Anglementioning
confidence: 99%